Novel (CoNiMgZn) xOLi1-x high-entropy oxide ceramic and preparation method thereof
Through mechanical ball milling method and SPS sintering technology, the preparation process of high-entropy oxide ceramics is simplified, the cost is reduced, and a large category of high-entropy oxide ceramics with excellent dielectric and superconducting properties is prepared, solving the problems of complex and high cost in the existing process.
Patent Information
- Application Number
- CN202510035692.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The preparation process of existing high-entropy oxide ceramics is complex, has high cost, and it is difficult to simplify the process to reduce production costs.
CoO, NiO, ZnO, MgO and Li2CO3 raw material powders were mixed in a specific molar ratio by mechanical ball milling, and (CoNiMgZn)xLi1-xO high-entropy oxide ceramics were prepared through ball milling, pre-pressing molding and discharge plasma sintering (SPS).
The preparation process is simplified, production costs are reduced, and a large class of high-entropy oxide ceramics with huge dielectric constants and ionic superconductivity are prepared through different raw material ratios, which are suitable for future energy and environmental materials.
Smart Images

Figure CN119707478A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a novel (CoNiMgZn)xOLi1-x high-entropy oxide ceramic and a preparation method thereof. Background Art
[0002] High entropy oxide ceramics are derived from high entropy alloys and are a new type of functional material. High entropy oxide ceramics are prepared by synthesizing five or more metal oxides in an equimolar ratio under certain temperature conditions to form a solid solution with a single-phase structure. High entropy oxide ceramic materials can be prepared by various synthesis methods, such as solid phase reaction method, spray pyrolysis method, field-assisted sintering method, polymer route synthesis method, co-precipitation method and hydrothermal synthesis method, solution combustion method and laser pulse method. Wang Hongjie et al. prepared uniform (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O high entropy oxide nanopowder. The method has the advantages of simple process, safety and reliability, low equipment requirements, relatively pure product, no impurity peaks, and uniform particle size of product particles [Wang Hongjie, Xu Liang, Su Lei, Peng Kang. A uniform high entropy oxide ceramic submicron spherical powder and preparation method thereof [P]. Shaanxi Province: CN110818430B, 2021-01-19.]. Liu Jinling et al. used 4 or less of the metal oxide powders MgO, ZnO, NiO, CuO, CaO, CoO, ZrO2, CeO2, Al2O3, Gd2O3, La2O3, Er2O3, Y2O3, Fe2O3, Co3O4, CaCO3 as raw materials, ball milled, dried, granulated and then pressed to obtain a green body and then heat treated, and then a high entropy oxide ceramic was prepared by flash sintering. Subsequent studies on (MgCoNiCuZn)O ceramics with a rock salt structure system found that they have excellent performance in Li ion conductivity, structural characteristics, catalysis, magnetic properties, electrical properties, thermal properties and mechanical properties [Liu Jinling, Liu Dianguang, Zhao Ke. A method for preparing high entropy oxide ceramics [P]. Sichuan Province: CN110204328A, 2019-09-06.]. Summary of the invention
[0003] The object of the present invention is to provide a novel (CoNiMgZn)xOLi1-x high entropy oxide ceramic and a preparation method thereof.
[0004] The high entropy oxide ceramic material is characterized in that the high entropy oxide ceramic material is based on metal oxides in an equal molar ratio, and the mass fraction of each component is 10-30wt.%.
[0005] The present invention also provides a new preparation method of high entropy oxide ceramic material. The preparation method of high entropy oxide ceramic material in the preparation process includes the following steps: S1, preparation of high entropy oxide ceramic powder; S2, pre-pressing and molding; S3, sintering preparation. Among them: S1. Preparation of high entropy oxide ceramic powder: CoO, NiO, ZnO, MgO and Li2CO3 raw material powders are weighed in a molar ratio of 1:1:1:1:(0.15-1.35), mixed and loaded into a corundum ball mill, zirconium oxide is used, the ball-to-material mass ratio is 10:1, the rotation speed is 350 r / min, the ball milling time is 10-40 h, and the machine is stopped for 30 min for heat dissipation every 1 h. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h, and then the ball milling is continued to obtain high entropy oxide ceramic powder; S2, pre-pressing: the mixed powder of step S1 is loaded into a mold for pre-pressing, the pre-pressing pressure is 300 MPa, the pre-pressing time is 1 min, and a pre-pressing raw material block is obtained; S3, sintering preparation: the pre-pressed block of step S2 is coated with cubic boron nitride and then placed in a graphite mold for spark plasma (SPS) sintering, with a vacuum degree of 40 Pa, a sintering pressure of 40 MPa, a sintering temperature of 900-1200 °C, a heating rate of 100 °C / min, and a holding time of 5-15 min. Then the temperature is lowered and the pressure is released to obtain (CoNiMgZn) x Li 1-x O high entropy oxide ceramic sintered body.
[0006] The SPS sintering process in step S3 is as follows: first, slowly apply pressure to the sample to 40 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 °C in 5 min, keep at 600 °C for 30 s; then heat from 600 °C to 900~1200 °C at a heating rate of 100 °C / min, and keep for 5~15 min. Cool with the furnace to obtain a sintered body. The prepared sintered body is subjected to surface grinding and deburring treatment to obtain (CoNiMgZn) x Li 1-x O high entropy oxide ceramics.
[0007] Furthermore, the particle size of the raw material CoO powder is <48 μm, the particle size of the NiO3 powder is 3~5 μm, the particle size of the ZnO powder is 1~3 μm, the particle size of the MgO powder is 1~2 μm, and the particle size of the Li2CO3 powder is 75 μm, and the purity of all raw material powders is ≥99.7%.
[0008] Furthermore, the diameters of the zirconia grinding balls used in the ball milling process were 8 mm, 5 mm, and 2 mm, respectively, and the mass ratio thereof was 6:3:1.
[0009] Compared with the prior art, the present invention has the following beneficial effects:
[0010] 1. The metal oxides selected in the present invention can be directly mixed by mechanical ball milling, and the materials can be taken out in the air after ball milling, which can simplify the preparation process to a certain extent and reduce the production cost.
[0011] 2. High entropy oxide ceramic sintered bodies were prepared using different raw material ratios, and their hardness was tested.
[0012] 3. High entropy oxides of this structural type have huge dielectric constants and ionic superconductivity, making them useful as dielectric materials and solid electrolytes for batteries in the future.
[0013] 4. The present invention provides a new preparation route for the preparation of nano high entropy oxide ceramics; the prepared nano high entropy oxide ceramic powder can be used in materials required for future energy and environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A process flow chart for preparing high entropy oxide ceramic materials; Figure 2 The XRD pattern of the raw material powder purchased in Example 1; Figure 3 The XRD pattern of the high entropy oxide ceramic powder prepared in Example 1; Figure 4 The XRD pattern of the high entropy oxide ceramic block prepared in Example 3; Figure 5 This is a surface SEM image of the high entropy oxide ceramic prepared in Example 3; Figure 6 This is a local SEM image of the fracture of the entropy oxide ceramic prepared in Example 3; Figure 7 The SEM images of high entropy oxide ceramics sintered at different temperatures prepared in Example 3; Figure 8 These are SEM images of high entropy oxide ceramics with different lithium carbonate contents prepared in Example 3. DETAILED DESCRIPTION
[0015] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0016] The invention provides a novel (CoNiMgZn)xOLi1-x high entropy oxide ceramic and a preparation method thereof.
[0017] High entropy ceramics originated from high entropy alloys, and then expanded into many types, high entropy oxide ceramics are one of them. High entropy oxide ceramics, also known as entropy-stabilized oxides, are a new type of functional material with a single-phase simple structure formed by five or more metal oxides in equal molar ratios under certain conditions. The high entropy oxide ceramic material is based on the metal oxides being in equal molar ratios, and its mass fraction is 10~30wt.%.
[0018] The present invention also provides a new preparation method of high entropy oxide ceramic material. The preparation method of high entropy oxide ceramic material in the preparation process includes the following steps: S1, preparation of high entropy oxide ceramic powder; S2, pre-pressing and molding; S3, sintering preparation. Among them: S1. Preparation of high entropy oxide ceramic powder: CoO, NiO, ZnO, MgO and Li2CO3 raw material powders are weighed in a molar ratio of 1:1:1:1:(0.15-1.35), mixed and loaded into a corundum ball mill, zirconium oxide is used, the ball-to-material mass ratio is 10:1, the rotation speed is 350 r / min, the ball milling time is 10-40 h, and the machine is stopped for 30 min for heat dissipation every 1 h. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h, and then the ball milling is continued to obtain high entropy oxide ceramic powder; S2, pre-pressing: the mixed powder of step S1 is loaded into a mold for pre-pressing, the pre-pressing pressure is 300 MPa, the pre-pressing time is 1 min, and a pre-pressing raw material block is obtained; S3, sintering preparation: the pre-pressed block of step S2 is coated with cubic boron nitride and then placed in a graphite mold for spark plasma (SPS) sintering, with a vacuum degree of 40 Pa, a sintering pressure of 40 MPa, a sintering temperature of 900-1200 °C, a heating rate of 100 °C / min, and a holding time of 5-15 min. Then the temperature is lowered and the pressure is released to obtain a (CoNiMgZn)xLi1-xO high entropy oxide ceramic sintered body.
[0019] The SPS sintering process in step S3 is as follows: first, slowly apply pressure to the sample to 40 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 °C in 5 min, keep at 600 °C for 30 s; then heat from 600 °C to 900~1200 °C at a heating rate of 100 °C / min, and keep for 5~15 min. Cool with the furnace to obtain a sintered body. The prepared sintered body is subjected to surface grinding and deburring treatment to obtain (CoNiMgZn)xLi1-xO high entropy oxide ceramics.
[0020] Furthermore, the particle size of the raw material CoO powder is <48 μm, the particle size of the NiO3 powder is 3~5 μm, the particle size of the ZnO powder is 1~3 μm, the particle size of the MgO powder is 1~2 μm, and the particle size of the Li2CO3 powder is 75 μm, and the purity of all raw material powders is ≥99.7%.
[0021] Furthermore, the diameters of the zirconia grinding balls used in the ball milling process were 8 mm, 5 mm, and 2 mm, respectively, and the mass ratio thereof was 6:3:1.
[0022] The following will be specifically described with reference to the embodiments: Example 1
[0023] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 10 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0024] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.526 g / cm 3 , hardness is 5.19 GPa, and there is no fracture toughness. Example 2
[0025] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0026] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.537 g / cm 3 , hardness is 5.95 GPa, and there is no fracture toughness. Example 3
[0027] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 30 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0028] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.531 g / cm 3 , hardness is 5.10 GPa, and there is no fracture toughness. Example 4
[0029] Four metal oxide powders, namely CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g), were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (rotation speed was 350 r / min, total ball milling time was 40 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0030] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.529 g / cm 3 , hardness is 4.98 GPa, and there is no fracture toughness. Example 5
[0031] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1000 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0032] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.521 g / cm 3 , hardness is 5.27 GPa, and there is no fracture toughness. Example 6
[0033] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1200 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0034] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.534g / cm 3 , hardness is 4.59GPa, and there is no fracture toughness. Example 7
[0035] Four metal oxide powders, CoO (2.317 g), MgO (1.246 g), NiO (2.309 g) and ZnO (2.516 g) and Li2CO3 powder (1.612 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 5 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0036] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.527 g / cm 3 , hardness is 4.41 GPa, and there is no fracture toughness. Example 8
[0037] Four metal oxide powders, CoO (2.553 g), MgO (1.373 g), NiO (2.544 g) and ZnO (2.772 g) and Li2CO3 powder (0.758 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials stuck to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 15 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0038] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.85 Li 0.15 O, its density is 5.46 g / cm 3 , hardness is 5.59 GPa, and there is no fracture toughness. Example 9
[0039] Four metal oxide powders, CoO (2.083 g), MgO (1.121 g), NiO (2.077 g) and ZnO (2.263 g) and Li2CO3 powder (2.455 g) were weighed respectively; CoO powder, MgO powder, NiO powder, ZnO powder and Li2CO3 powder were loaded into a corundum ball mill, and yttrium-stabilized zirconia balls were added according to the ball-to-material mass ratio of 10:1, and ball milling was carried out in an argon atmosphere (the speed was 350 r / min, the total ball milling time was 20 h, and the machine was stopped for 20 min every 1 h for heat dissipation), and the raw materials adhering to the grinding balls and the inner wall of the jar were scraped off and mixed every 10 h, and then 0.2 ml / 10 g of the mixed powder was added as an anhydrous ethanol dispersant and the ball milling was continued) to obtain high entropy oxide ceramic material powder; the diameters of the steel grinding balls were 8 mm, 5 mm and 2 mm, respectively. mm, the mass ratio of large, medium and small balls is 6:3:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 300 MPa, and the pre-pressing is 1 min. Then spark plasma sintering is carried out, the vacuum degree is 40 Pa, and the pressure is increased to 50 MPa; then, it is heated from room temperature to 600 ℃ in 5 min, and kept at 600 ℃ for 30 s; then it is heated from 600 ℃ to 1100 ℃ at a heating rate of 100 ℃ / min, and kept for 10 min. Cooling with the furnace, a blank is obtained. The surface of the blank is ground and polished to obtain a high-temperature resistant metal ceramic-based self-lubricating composite material.
[0040] The obtained high entropy oxide ceramic material sample was polished and then tested for performance. The obtained sintered body was (CoNiMgZn) 0.77 Li 0.23 O, its density is 5.51 g / cm 3 , hardness is 5.34 GPa, and there is no fracture toughness.
[0041] Taking Example 1, Example 5 and Example 7 as examples, TiC-14wt.%TiC 0.4 The XRD patterns of the sintered bodies of TiC-7.63wt.%Ti and 9TiC-0.5Ti-0.5Zr only contain TiCx peaks, indicating that the added metals are all dissolved in TiC. Due to the low addition amount, the peak of the generated solid solution cannot be detected or the solid solution peak overlaps with the TiC peak. From the surface morphology, it can be seen that the sintered body has a high degree of densification, no obvious pores are seen, and there are crack deflection and bridging. TiC 0.4 The addition of plays a role in strengthening the bonding strength between grains, and the fracture morphology of the sintered body shows that its fracture mode is transgranular fracture.
[0042] It can be seen from Examples 1-7 that the mechanical alloying time, sintering temperature and TiC 0.4The addition of V and Zr has a significant effect on the properties of TiC composite ceramics. The addition of metal V and Zr further improves the properties of TiC. 0.4 The hardness of the composite ceramic is significantly reduced and the toughness is improved. It can be seen from Examples 1 and 3 that as the sintering temperature increases from 1600°C to 1700°C, the TiC-14wt.%TiC 0.4 The hardness of the composite ceramic decreases significantly, and the toughness also decreases slightly. It can be seen from Examples 5 and 7 that the addition of metal Zr significantly improves the fracture toughness of the TiC-Ti composite ceramic while maintaining high hardness.
[0043] In summary, the metal oxides selected in the present invention can be directly mixed by mechanical ball milling, and the materials can be taken out in the air after ball milling, which can simplify the preparation process to a certain extent and reduce the production cost. High entropy oxide ceramic sintered bodies were prepared by using different raw material ratios, and their hardness was tested. This type of high entropy oxide has a huge dielectric constant and ionic superconductivity, so that high entropy oxide can be used as a dielectric material and battery solid electrolyte in the future. The present invention provides a new preparation route for the preparation of nano high entropy oxide ceramics; the prepared nano high entropy oxide ceramic powder can be used in materials required for future energy and environment.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A new type (CoNiMgZn) x Li 1-x O high entropy oxide ceramics, characterized in that It is a new functional material with a single-phase simple structure formed by five or more metal oxides in equal molar ratios, and the high-entropy oxide ceramic material is based on the metal oxides being in equal molar ratios, and their mass fraction is 10-30wt.%.
2. The novel (CoNiMgZn) according to claim 1 x Li 1-x O high entropy oxide ceramics, characterized in that: The metal oxide single substance powders included in the high entropy oxide ceramic material include: MgO, CoO, NiO, and ZnO.
3. The novel (CoNiMgZn) according to claim 2 x Li 1-x O high entropy oxide ceramics, characterized in that: The high entropy oxide ceramic further includes other compounds, wherein the other compounds include alkaline earth elements (Li) added in the form of lithium carbonate.
4. The novel (CoNiMgZn) according to claim 3 x Li 1-x O high entropy oxide ceramics, characterized in that: The metal oxides and lithium carbonate are commercially available.
5. A novel (CoNiMgZn) as claimed in claim 1 x Li 1-x A method for preparing high entropy oxide ceramics, characterized in that: The steps include: S1. Preparation method of high entropy oxide ceramic powder: In a glove box filled with argon, CoO, NiO, ZnO, MgO and Li2CO3 are mixed in a molar ratio of 1:1:1:1:0.35 and loaded into a corundum ball mill, and zirconium oxide grinding balls are used. The material mass ratio is 10:1, the rotation speed is 350 r / min, the ball milling time is 10 to 40 hours, and the machine is stopped for 30 minutes every 1 hour to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 hours, and then the ball milling is continued to obtain high entropy oxide ceramic powder; S2, pre-pressing: drying the mixed powder in an argon atmosphere, and loading it into a mold for pre-pressing, wherein the pre-pressing pressure is 300 MPa, and the pre-pressing is performed for 1 to 3 min to obtain a pre-pressed raw material block; S3, sintering preparation: the block pre-pressed in step S2 is coated with cubic boron nitride and then placed in a graphite mold and then subjected to spark plasma sintering, with a vacuum degree of 40 Pa, a sintering pressure of 40 MPa, a sintering temperature of 900-1200°C, a heating rate of 100°C / min, and a holding time of 5-15 min; then the temperature is reduced and the pressure is released to obtain (CoNiMgZn) x OLi 1-x High entropy oxide ceramic sintered body.
6. The novel (CoNiMgZn) according to claim 5 x Li 1-x The method for preparing a high entropy oxide ceramic material is characterized in that: The purity of the CoO, NiO, ZnO and MgO powders is greater than 99%, wherein the particle size of the NiO, MgO and ZnO powders is 1 to 5 μm, and the particle size of the CoO powder is less than 48 μm.
7. The novel (CoNiMgZn) according to claim 3 x Li 1-x A method for preparing high entropy oxide ceramics, characterized in that: The particle size of the Li2CO3 powder is 75-100 μm, and the purity is >99%.
8. The novel (CoNiMgZn) according to claim 3 x Li 1-x A method for preparing high entropy oxide ceramics, characterized in that: The ball milling processes of steps S1, S2 and S3 all use yttrium-stabilized zirconia grinding balls of three sizes, large, medium and small, with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small grinding balls is 6:3:
1.
9. The novel (CoNiMgZn) according to claim 3 x Li 1-x A method for preparing high entropy oxide ceramics, characterized in that: The specific sintering process in step S3 is as follows: first, slowly apply pressure to the sample to 40 MPa; then, evacuate to 80-200 Pa; then, heat from room temperature to 600 ° C for 5 min, and keep at 600 ° C for 30 s; then, heat from 600 ° C to 900-1200 ° C at a heating rate of 100 ° C / min, and keep for 5-15 min; cool with the furnace to obtain a sintered body; perform surface grinding and deburring on the prepared sintered body to obtain (CoNiMgZn) x Li 1-x O high entropy oxide ceramic materials.
Citation Information
Patent Citations
Preparation method of high-entropy oxide ceramic
CN110204328A